2021
DOI: 10.3847/1538-4357/abbcd6
|View full text |Cite
|
Sign up to set email alerts
|

Re-estimating the Spin Parameter of the Black Hole in Cygnus X-1

Abstract: Cygnus X-1 is a well-studied persistent black hole X-ray binary. Recently, the three parameters needed to estimate the black hole spin of this system, namely the black hole mass M, the orbital inclination i, and the source distance D, have been updated. In this work we redetermine the spin parameter using the continuum-fitting technique for those updated parameter values. Based on the assumption that the spin axis of the black hole is aligned with the orbital plane, we fit the thermal disk component to a fully… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…Other pathways to fastspinning BH progenitor stars, in single or binary systems, have been proposed to lead to LGRBs (e.g., Yoon et al 2006;Cantiello et al 2007), albeit none at a rate that matches the observed one when considering efficient AM transport in stellar interiors (Fryer et al 2007). Observed high-mass X-ray binaries that contain fast-spinning BHs, such as Cygnus X-1 (e.g., Gou et al 2011;Zhao et al 2021), may have also been progenitors of LGRBs. The formation of these systems is puzzling (e.g., Wong et al 2012;Neijssel et al 2021), and it is uncertain whether the BH spin in these systems originates from fast-spinning pre-collapse cores (see, e.g., Moreno Méndez et al 2008;Batta et al 2017;Schrøder et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways to fastspinning BH progenitor stars, in single or binary systems, have been proposed to lead to LGRBs (e.g., Yoon et al 2006;Cantiello et al 2007), albeit none at a rate that matches the observed one when considering efficient AM transport in stellar interiors (Fryer et al 2007). Observed high-mass X-ray binaries that contain fast-spinning BHs, such as Cygnus X-1 (e.g., Gou et al 2011;Zhao et al 2021), may have also been progenitors of LGRBs. The formation of these systems is puzzling (e.g., Wong et al 2012;Neijssel et al 2021), and it is uncertain whether the BH spin in these systems originates from fast-spinning pre-collapse cores (see, e.g., Moreno Méndez et al 2008;Batta et al 2017;Schrøder et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The primary in GW200115 may even have relatively high spin, with a 90% upper limit of 0.72. Several studies of the observed population of high-mass X-ray binaries (Liu et al 2008;Gou et al 2009Gou et al , 2014Zhao et al 2021) find that the BHs have large spins (Valsecchi et al 2010;Wong et al 2012;Qin et al 2019;Zhao et al 2021). Given the short lifetime of the secondary, mass transfer is argued to be insufficient to generate BHs with such high spins, implying that the BHs were born with high spins.…”
Section: Spinsmentioning
confidence: 99%
“…The BH mass, the inclination and the distance of the system was estimated to be 21.2±2.2 M ⊙ , 27.51°+ 0.77 −0.57 , and 2.22 +0.18 −0.17 kpc using VLBA observations (Miller-Jones et al 2021). The dimensionless spin parameter of the BH a * was estimated as ∼ 0.998 (Zhao et al 2021;Kushwaha et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cyg X-1 exhibits one of the best established examples of relativistic reflection study, especially in the soft state (Duro et al 2011;Fabian et al 2012). Many studies on Xray reflection of Cyg X-1 have constrained the characteristic properties of the system such as the Fe abundance of the disk, the inner disk radius or the spin of the BH (Zhao et al 2021;Walton et al 2016;Tomsick et al 2014;Basak et al 2017).…”
Section: Introductionmentioning
confidence: 99%